Plasma amyloid beta levels and platelet mitochondrial respiration in patients with Alzheimer's disease - Fišar, Zdeněk; Jirák, Roman; Zvěřová, Martina; Setnička, Vladimír; Habartová, Lucie; Hroudová, Jana; Vaníčková, Zdislava; Raboch, Jiří (Clinical biochemistry, 2019)
OBJECTIVES: Altered amyloid metabolism and mitochondrial dysfunction play key roles in the development of Alzheimer's disease (AD). We asked whether an association exists between disturbed platelet mitochondrial respiration and the plasma concentrations of Aβ40 and Aβ42 in patients with AD. DESIGN AND METHODS: Plasma Aβ40 and Aβ42 concentrations and mitochondrial respiration in intact and permeabilized platelets were measured in 50 patients with AD, 15 patients with vascular dementia and 25 control subjects. A pilot longitudinal study was performed to monitor the progression of AD in a subgroup 11 patients with AD. RESULTS: The mean Aβ40, Aβ42 and Aβ42/Aβ40 levels were not significantly altered in patients with AD compared with controls. The mitochondrial respiratory rate in intact platelets was significantly reduced in patients with AD compared to controls, particularly the basal respiratory rate, maximum respiratory capacity, and respiratory reserve; however, the flux control ratio for basal respiration was increased. A correlation between the plasma Aβ42 concentration and mitochondrial respiration in both intact and permeabilized platelets differs in controls and patients with AD. CONCLUSIONS: Based on our data, (1) mitochondrial respiration in intact platelets, but not the Aβ level itself, may be included in a panel of biomarkers for AD; (2) dysfunctional mitochondrial respiration in platelets is not explained by changes in plasma Aβ concentrations; and (3) the association between mitochondrial respiration in platelets and plasma Aβ levels differs in patients with AD and controls. The results supported the hypothesis that mitochondrial dysfunction is the primary factor contributing to the development of AD.
Keywords: biologické markery; Plasma; lidé; Middle Aged; Amyloid beta-Peptides; mitochondriální nemoci; Female; amyloidní beta-protein; buněčné dýchání; Alzheimerova nemoc; Humans; peptidové fragmenty; mitochondrie; lidé středního věku; Biomarkers; Platelet; mužské pohlaví; Alzheimer Disease; Mitochondria; Cell Respiration; ženské pohlaví; Amyloid beta; Peptide Fragments; spotřeba kyslíku; Male; Aged; Mitochondrial Diseases; Oxygen Consumption; Alzheimer's disease; senioři